Nègènègèn: Sweet talk, disrespect, and abuse among rural auxiliary midwives in Mali. Issue 11 (November 2015) - Warren, Nicole; Beebe, Madeleine; Chase, Rachel P.; Doumbia, Seydou; Winch, Peter J.
Abstract: Objective: the purpose of this study was to explore disrespect and abuse toward women in labor from the perspective of auxiliary midwives. Design: this study uses a cross-sectional, descriptive mixed-methods design using surveys and interviews. Setting: Koutiala, Mali. Participants: 67 mostly rural auxiliary midwives. Interventions: this was a descriptive study and had no intervention component. The variables of interest were Malian auxiliary midwives׳ reports of caring and respectful, as well as abusive and disrespectful, behaviours towards childbearing women. Findings: participants reported abusive and disrespectful behaviour toward women, particularly yelling, insulting, and displaying a hostile or aggressive attitude. However, auxiliary midwives also stressed the importance of making women feel welcome and comfortable, sweet-talking to them throughout labor, and providing quality care. Implications for training and practice: we recommend a strengths-based approach to pre-service and continuing education to ensure that auxiliary midwives meet the basic competencies for midwives and appreciate both the impact of their abusive and disrespectful behaviours and the value of the respectful care they already provide. Highlights: We interviewed 67 mostly rural auxiliary midwives in Mali, West Africa Midwives reported abusive and disrespectful behavior. Midwives used verbal strategies to make women feel comfortable and welcome. Midwives may not appreciate the impact of abusive/disrespectful behaviours. A strengths-based approach to training can reinforce positive, existing behaviours.